The perverse effect of sin taxes: The rise of illicit white cigarettes - Aparna Mathur; Roger Bate; Cody Kallen (American Enterprise Institute (AEI), 2017)
This paper analyzes whether taxes create a price wedge between legal and illicit cigarettes and thereby affect the availability and trade of illicit whites across markets.
Keywords: A; 330; tax reform; cigarettes